Utility of Whole Exome Sequencing for Genetic Diagnosis of Previously Undiagnosed Pediatric Neurology Patients. (December 2016) - Kuperberg, Maya; Lev, Dorit; Blumkin, Lubov; Zerem, Ayelet; Ginsberg, Mira; Linder, Ilan; Carmi, Nirit; Kivity, Sarah; Lerman-Sagie, Tally; Leshinsky-Silver, Esther
Whole exome sequencing enables scanning a large number of genes for relatively low costs. The authors investigate its use for previously undiagnosed pediatric neurological patients. This retrospective cohort study performed whole exome sequencing on 57 patients of "Magen" neurogenetic clinics, with unknown diagnoses despite previous workup. The authors report on clinical features, causative genes, and treatment modifications and provide an analysis of whole exome sequencing utility per primary clinical feature. A causative gene was identified in 49.1% of patients, of which 17 had an autosomal dominant mutation, 9 autosomal recessive, and 2 X-linked. The highest rate of positive diagnosis was found for patients with developmental delay, ataxia, or suspected neuromuscular disease. Whole exome sequencing warranted a definitive change of treatment for 5 patients. Genetic databases were updated accordingly. In conclusion, whole exome sequencing is useful in obtaining a high detection rate for previously undiagnosed disorders. Use of this technique could affect diagnosis, treatment, and prognostics for both patients and relatives.